Advances in bladder preservation therapy for muscle-invasive bladder cancer - Zhang, Ran; Ke, Chang-Xing (Frontiers in Oncology, 2025)
Bladder cancer is one of the most common genitourinary malignancies. Radical cystectomy (RC) and pelvic lymphadenectomy (PLND) after neoadjuvant chemotherapy have become the accepted gold standard for the treatment of resectable muscular invasive bladder cancer due to its ability to surgically remove tumor tissue as thoroughly as possible and reduce the risk of tumor recurrence and metastasis, thus improving patient survival. However, RC surgery is challenging and associated with many postoperative complications, requiring patients to have good physical condition to tolerate the procedure. Over the years, with the deepening of medical research and the accumulation of clinical practice, the disease spectrum of bladder cancer has changed significantly. At the same time, the treatment modalities for bladder cancer have also been continuously improved and updated, and bladder-preserving treatment programs have gradually emerged and demonstrated reliable efficacy. Bladder-sparing treatment aims to preserve the physiological function of the bladder while controlling tumor growth, thereby improving patients’ quality of life. This approach has led an increasing number of MIBC patients to choose bladder-sparing treatment after considering their individual conditions. In this paper, we review the current methods of bladder-sparing treatment for MIBC patients and related studies to provide a reference for future research.